The Influence of Internal Control Systems and Financial Managers' Competence on Local Government Financial Report Quality with Internal Transparency as a Mediator - Darmono, Darmono; Ramdiska, Rizki; Sappewali, Badriah; Perdana Kusuma Putra, Aditya Halim (Universitas Dharma Wacana, 2024)
This research aims to develop a model for improving the financial quality of local governments through internal transparency with independent variables of the internal control sistem and the competence of financial officials. This type of research is an explanatory research with data sources using primary and secondary data. The primary data in this study includes the perception of financial management officials related to the internal control sistem, the competence of financial management officials, internal transparency, and the quality of local government financial reports. Secondary data includes the identity of the respondents obtained from the SKPD of the Berau Regency Regional Government and literature review as a reference for literature related to the research. The population of this study is the Regional Apparatus Work Unit (SKPD) of the Regional Government of Berau Regency with 46 SKPDs. The sampling method of this study uses a saturated sample technique (census) with each SKPD represented by 3 respondents so that the total sample is 138 respondents. The analysis technique of this study uses an alternative method of Structural Equational Modelling (SEM) using AMOS Software. The results of this study show that the internal control sistem and the competence of financial management officials have a significant positive effect on internal transparency. The internal control sistem has a positive and significant effect on the quality of local government financial reports and the competence of financial management officials has a positive but not significant effect on the quality of local government financial statements. Internal transparency has a significant positive effect on the quality of local government financial statements. The internal control sistem and the competence of financial management officials on the quality of local government financial reports through internal transparency have an indirect and significant influence.